Mapping of Digitaria streak virus transcripts reveals different RNA species from the same transcription unit. - Accotto, G P (EMBO J, 1989)
All, except 19 [corrected] bp, of the Digitaria streak virus (DSV) genome is transcribed. Two RNA transcripts (1+ and 2+) are encoded by the virion DNA strand and up to five (1- to 5-) by the complementary DNA strand [corrected]. Detailed mapping of these RNAs has revealed evidence for splicing in one species (RNA 4-), which together with its more abundant unspliced counterpart (RNA 2-) could synthesize both a 30.5 and 41 kd polypeptide from the same transcription unit. This extensive overlapping of spliced and unspliced RNAs could indicate that the initiation and splicing of transcripts is temporally regulated. At least one transcript (RNA 1-) may have a non-translational role. Transcription of the DSV genome shows similarities to some animal DNA viruses, particularly the papovaviruses. IMAGES: